2012
DOI: 10.1097/sih.0b013e3182614f95
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Technology-Enhanced Simulation Versus Other Instructional Methods

Abstract: To determine the comparative effectiveness of technology-enhanced simulation, we summarized the results of studies comparing technology-enhanced simulation training with nonsimulation instruction for health professions learners. We systematically searched databases including MEDLINE, Embase, and Scopus through May 2011 for relevant articles. Working in duplicate, we abstracted information on instructional design, outcomes, and study quality. From 10,903 candidate articles, we identified 92 eligible studies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(178 citation statements)
references
References 35 publications
(27 reference statements)
5
167
0
6
Order By: Relevance
“…Certain study subgroups were absent or present in lower proportions compared with the larger cohort from which this sample was extracted, [13][14][15] including nonprocedural activities such as physical exam, patient counseling, or clinical reasoning; procedures such as surgery and anesthesiology; and some learner groups (notably medical students). This suggests selection bias in the topics and learners represented.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Certain study subgroups were absent or present in lower proportions compared with the larger cohort from which this sample was extracted, [13][14][15] including nonprocedural activities such as physical exam, patient counseling, or clinical reasoning; procedures such as surgery and anesthesiology; and some learner groups (notably medical students). This suggests selection bias in the topics and learners represented.…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…71,[80][81][82][83][84][85][86] These comparisons with active interventions were included in previous meta-analyses. 14,15 Three articles omitted the number of trainees; we contacted these authors and two provided needed information.…”
Section: Trial Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation-based training allows trainees to practice skills in a low-pressure environment, without risk to patients, and allows trainees to make and learn from mistakes before they occur in surgery [13]. Previous research has shown that simulation can be highly effective for learning technical and nontechnical surgical skills [3,4,9,[14][15][16][17] and that the skills learned can transfer to clinical settings [5]. Furthermore, simulation-based training can shorten the learning curve, enhance later intraoperative learning [8,14], and improve patient outcomes [19].…”
Section: Introductionmentioning
confidence: 99%
“…In health education, there is growing evidence that simulation improves learners' safety [1], competence, and skills [2], especially when compared to traditional didactic methods and/or no simulation training [3]. Of significant importance to the health profession is airways management [4], where inadequate skill and poor judgment can lead to patient complications and death [5].…”
Section: Introductionmentioning
confidence: 99%